Pre-Modern Citizenship: An Ancient Concept for the Modern World? - Withington, Phil (TSEG - The Low Countries Journal of Social and Economic History, 2020)
This article discusses the challenges and opportunities of turning to the pre-modern world to address contemporary problems. To do so it compares Maarten Prak’s approach to practical citizenship in Citizens without nations with Jurgen Habermas’s infamous evocation of the ‘bourgeois public sphere’. While different in important respects – not least in terms of the kind of historical citizenship they recover and the methods by which they do it – Prak and Habermas nevertheless share an important similarity. This is that both are quite idealistic, in an aspirational sense, about how their pre-modern forms of citizenship can benefit and improve the modern world. This sense of idealism can be contrasted with Max Weber’s preference for excavating ideal types that described, for better or worse, the normative values and behaviours of particular cultures in the past. This response then outlines the normative practices of Prak’s citizenship and asks whether they are really commensurate with modern life.